Relationship of hypoglycemia and glucose variability with autonomic dysfunction in children and adolescents with type 1 diabetes - Dmitriy Nikitich Laptev (Сахарный диабет)
Aim. Glucose variability (GV) and hypoglycaemia frequency and duration, depending on cardiovascular autonomic dysfunction, in children and adolescents with type 1 diabetes mellitus (T1DM) were evaluated. Materials and methods. One hundred and thirty T1DM patients, aged 6?18 years, were included in this study. The study included 3 tests:. continuous glucose monitoring (CGM) with GV evaluation, frequency and duration of hypoglycaemia;24-h ECG monitoring with automatic calculation of QTc interval and heart rate variability (HRV) parameters;cardiovascular autonomic tests.Results. The estimated prevalence of cardiovascular autonomic neuropathy (CAN) was 19.2%. CAN positive (CAN+) patients had lower values from cardiovascular autonomic tests and HRV and longer QTc intervals compared with CAN negative (CAN-) patients (p